In silico evaluation of Vitis amurensis Rupr. Polyphenol compounds for their inhibition potency against COVID-19 main enzymes Mpro and RdRp - Imen Souid; Atef Korchef; Safouan Souid (Saudi Pharmaceutical Journal, 2022)
The rapid transmission of the pneumonia (COVID-19) emerged as an entire worldwide health concern and it was declared as pandemic by the World Health Organization (WHO) as a consequence of the increasing reported infections number. COVID-19 disease is caused by the novel SARS-CoV-2 virus, and unfortunatly no drugs are currently approved against this desease. Accordingly, it is of outmost importance to review the possible therapeutic effects of naturally-occuring compounds that showed approved antiviral activities. The molecular docking approach offers a rapid prediction of a possible inhibition of the main enzymes Mpro and RdRp that play crucial role in the SARS-CoV-2 replication and transcription. In the present work, we review the anti-viral activities of polyphenol compounds (phenolic acids, flavonoids and stilbene) derived from the traditional Chinese medicinal Vitis amurensis. Recent molecular docking studies reported the possible binding of these polyphenols on SARS-CoV-2 enzymes Mpro and RdRp active sites and showed interesting inhibitory effects. This antiviral activity was explained by the structure-activity relationships of the studied compounds. Also, pharmacokinetic analysis of the studied molecules is simulated in the present work. Among the studied polyphenol compounds, only five, namely caffeic acid, ferulic acid, quercetin, naringenin and catechin have drug-likeness characteristics. These five polyphenols derived from Vitis amurensis are promising drug candidates for the COVID-19 treatment.